Makna Rangkap Jabatan dalam Pencapaian Produktivitas yang Optimal Pada PT Barito Sarana Karya Gresik - Rini Wulani Aisyah; Budi Pristyadi (Universitas Muhammadiyah Gresik, 2021)
Background - The minimum number of workers employed in the company means that there are several employees who work in two positions. However, with these dual positions, work productivity remains optimal. Objective - This study aims to determine the meaning of dual positions in achieving optimal productivity at PT Barito Sarana Karya Gresik. Design/Methodology/Approach - Researchers use a qualitative approach. The informants in this study were 3 informants, where there were 2 key informants and 1 supporting informants. Data collection is carried out by interview and documentation. Test the validity of the data by using source triangulation and membercheck. Findings - The results of research conducted in the field show that workers who hold concurrent positions interpret dual positions in 4 themes, namely workload, constrains, discipline, and compensation received. So that the 4 themes can produce optimal work productivity even though working more than one job is done. Research implications - This research can be used as a source of information related to the management of human resource management, especially dual positions. Research limitations - This study only reveals the meaning of multiple positions in one company so that it is less able to compare the meaning of multiple positions for each company.